Measuring the characteristics among critical success factors of PPP infrastructure projects - A. Khalifa, Nasradeen; A. A. Hmedab, Alsnose; Roslan Zainal Abidin; Milad, Abdalrhman (Penerbit Universiti Kebangsaan Malaysia, 2021)
Private-Public Partnership (PPP) is an increasingly popular choice for policymakers in implementing critical public projects through the examination of essential factors of success of PPP and establishing an empirical model of PPP in the construction project in Malaysia. The PPP implementation model was hypothesised to investigate the measurements and dimensions of technology, Organisational, and project characteristics as critical success factors of PPP implementation. A quantitative methodology was employed to validate the measurements, hypothesis testing and validate a structural model of PPP implementation. A total of 238 respondents was involved in the survey of the hypothesised PPP model. SPSS version 22 as well as Analysis of Moment Variance (AMOS) software were employed to analyse the data gathered. Path analysis and mediated regression analysis of the structural equation model succeeded in determining the mediating effect of stakeholder and procurement on the relationship among critical success factors and PPP implementation. The overall results show a significant positive interaction of Organisational, technical, and project characteristics as essential factors of success on stakeholder and procurement as a mediator on the achievement of PPP implementation. This paper highlights not only the vital success factors for PPP but also offers a fundamental contribution model achieved through the empirical model of critical success factors and PPP implementation in the construction project in Malaysia. This study succeeds in establishing and validating a structural model of the PPP implementation model. The model contributes to the body of knowledge of PPP and benefits to practitioners as primary guidance on construction and business developments.